Monitoring venture capital investments through internal control prediction markets - Max Werner; Andrea Vianelli; Mariusz C. Bodek (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
This paper offers a new perspective on a fundamental issue of venture capital investments, i.e., the so-called black box of involvement that concerns the paucity of relevant information necessary for venture capital managers to evaluate investments properly. Our paper discusses the application of an internal control prediction market as a monitoring instrument for venture capital investments. We therefore gather research literature and law and financial expertise to discuss uncertain business developments, missing data, and principal-agent conflicts. The results of our paper are expected to make significant contributions to the academic discussion, providing a foundation to open the black box of involvement that current venture capital managers face daily.
Keywords: G32; G34; G39; 330; Venture Capital; Venture; Capital Investments; Seed Capital; Monitoring; Managing; Black Box